2007
DOI: 10.1080/17470910701376811
|View full text |Cite
|
Sign up to set email alerts
|

Action during body perception: Processing time affects self–other correspondences

Abstract: The accurate perception of other people and their postures is essential for functioning in a social world. Our own bodies organize information from others to help us respond appropriately by creating self-other mappings between bodies. In this study, we investigated mechanisms involved in the processing of self-other correspondences. Reed and Farah (1995) showed that a multimodal, articulated body representation containing the spatial relations among parts of the human body was accessed by both viewing another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 55 publications
1
27
0
2
Order By: Relevance
“…Furthermore, behavioral studies showed an influence of action observation on action execution (Brass, Bekkering, Wohlschlager, & Prinz, 2000;Brass, Bekkering, & Prinz, 2001;Kilner, Paulignan, & Blakemore, 2003;Stürmer, Aschersleben, & Prinz, 2000) and visa verse (Jacobs & Shiffrar, 2005;Reed & Farah, 1995;Reed & McGoldrick, 2007). However, although these findings provide insight into the underlying representations of action perception, little is known about the exact timing of the proposed action simulation process.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, behavioral studies showed an influence of action observation on action execution (Brass, Bekkering, Wohlschlager, & Prinz, 2000;Brass, Bekkering, & Prinz, 2001;Kilner, Paulignan, & Blakemore, 2003;Stürmer, Aschersleben, & Prinz, 2000) and visa verse (Jacobs & Shiffrar, 2005;Reed & Farah, 1995;Reed & McGoldrick, 2007). However, although these findings provide insight into the underlying representations of action perception, little is known about the exact timing of the proposed action simulation process.…”
Section: Introductionmentioning
confidence: 88%
“…In one of many experiments demonstrating this effect, Reed and McGoldrick (2007) asked observers to judge whether two sequentially presented pictures of body postures were the same or different; in some of the trials, the leg posture differed in the two pictures; in others, the arm posture differed. While observers were making their judgments about the postures, they planned and produced movements with either their arms or legs.…”
mentioning
confidence: 99%
“…Reed & McGoldrick, 2007; Reed & Farah, 1995) to investigate whether the listener’s motor system is involved in processing a speaker’s gestures. Gestures do not require a physical response from the listener.…”
mentioning
confidence: 99%
“…Typically, behavior and brain activity are tested in a prone/seated position, although many or even most interactions with humans occur in the standing or walking position (Parsons, 1987;Arzy et al, 2006;Reed and McGoldrick, 2007), and brain mechanisms may differ depending on the body position (Gaunet and Berthoz, 2000;Arzy et al, 2006;Lobmaier and Mast, 2007). Moreover, most neuroimaging studies [i.e., functional magnetic resonance imaging (fMRI) or positron emission tomography (PET)] are performed in the supine position.…”
Section: Introductionmentioning
confidence: 99%